Justice : a beginner's guide - Wacks, Raymond (London, England : Oneworld, 2017)
Professor Raymond Wacks breaks down the leading theories of justice and illustrates how present-day challenges, like terrorism and migration, affect our fundamental notions of fairness and democratic freedoms.
Justice and injustice -- Justice and virtue -- Rights, dignity and freedom -- Utilitarianism -- Justice as fairness -- Libertarianism -- Capability -- Justice and the free market -- Equality -- Fraternity -- Communitarianism -- Global justice -- Achieving social justice -- Some key terms.
"A Oneworld Paperback Original."
Includes bibliographical references (pages 194-207) and index.
Keywords: Justice, Administration of; Fairness; Equality before the law; Justice -- Popular works